Inheritance Rights in Interfaith Marriages According to Inheritance Law - Elle Tasya Putri; Benny Djaja (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Marriage is an important event in everyone's life. But in reality, there are still many people who marry with different religions, which in the end interfaith marriages create various kinds of problems, such as a person's part in obtaining inheritance or what is also known as an inheritance from heirs of different religions will be affected or participate. change, besides that the problem that often occurs because of interfaith marriages is that a person cannot get an inheritance because the rules of each inheritance law that apply and regulate inheritance have their own rules which are different from one another. In writing this law, it will be explained what is the position of a person as in decision number 16 K/AG/2010 which is used as an example in writing this law, and how the suitability between the decision given by the judge and the inheritance regulations that exist and apply in Indonesia. the author will use the Normative Juridical Method/literature review by reading and analyzing both books, articles, the internet, and applicable laws and regulations. The brief conclusion that the author can give here is that the position of a person who has a different religion from the heir to get an inheritance can be determined by the rules contained in each inheritance law, and the suitability between the judge's decision given in decision Number 16 K/AG/2010 Even though the judge has reformed the law by giving a mandatory will to heirs of different religions,  The obligatory will cannot be blamed because the obligatory will itself has the goal of obtaining justice